Traces of Manufacture, Use, Repair and Modification Observed on Ethnographic Throwing Sticks and Boomerangs - Luc Bordes (EXARC Journal)
Throwing sticks and boomerangs are present in the collections of many French and international museums. Collected mainly in the 19th and 20th centuries by travelers, they were mainly analyzed from a stylistic point of view, to relate them to their region of origin. Some of these objects were made by the indigenous populations especially to be exchanged with Europeans and only bear macro-traces of manufacture. However, many others can have additional various traces of use and repair which reflect a real function and which are often less studied. Indeed, these traces can shed light on the functionality of the object in relation to their physical characteristics, which determine their aerodynamic properties. However, these throwing weapons were not only used as projectiles. In some cases, a major modification of the object may have taken place to adjust it for a new use.